Prenatal Weight Change Trajectories Among Women With Obesity. (7th June 2021) - Nichols, Amy; Hedderson, Monique; Xu, Fei; Foster, Saralyn; Rickman, Rachel; Widen, Elizabeth
Abstract: Objectives: Current gestational weight change (GWC) recommendations were established by the Institute of Medicine (IOM) with limited evidence for pattern and timing of weight change across pregnancy. Likewise, the recommendation of 5–9kg for women with obesity does not differentiate by severity of obesity. We sought to describe GWC trajectory patterns among a large, contemporary cohort of women with obesity. Methods: Electronic medical records were abstracted for 22, 987 women with obesity (BMI ≥ 30.0) who delivered a singleton pregnancy at Kaiser Permanente Northern California between 2008–2013. We modeled GWC for women with a measured prepregnancy weight, at least three prenatal visit weights, and a normal oral glucose tolerance test at 20 wk gestation. Weight change trajectories were modeled using flexible latent class mixed modeling (package LCMM) in R. Results: Before pregnancy, 60.4% of women had class 1 obesity (BMI 30.0–34.9kg/m 2 ), 24.8% class 2 (35.0–39.9), and 14.8% class 3 (≥40.0). Most women identified as White (37.3%) or Hispanic (37.3%), with 12.4% Black and 8.5% Asian. Five GWC trajectory groups across pregnancy were identified, each with a distinct pattern of weight change before 15 wk followed by weight gain thereafter (<15 wk/>15 wk): 12.2% exhibited HighLoss/SteadyGain with mean GWC at delivery of 0.9 ± 3.1kg (mean ± sd); 25.8% LowLoss/SteadyGain (6.4 ± 2.4); 30.4% LowGain/ModerateGain (11.4 ± 2.5); 23.0% ModerateGain/HighGain (16.8 ± 3.1); and 8.6% HighGain/HighGain (24.5 ± 5.0). Prepregnancy obesity classes were represented across GWC trajectory groups but were predominantly in two groups: those with class 1 obesity exhibited LowGain/ModerateGain (32.1%), class 2 was split between LowGain/ModerateGain (29.0%) and LowLoss/SteadyGain (28.8%), and class 3 exhibited LowLoss/SteadyGain (31.8%). Only the LowLoss/SteadyGain (25.8%) group demonstrated total GWC at delivery within the IOM recommendation. Conclusions: Among women with obesity, GWC was not linear or uniform, and current recommendations do not reflect nuances of the prenatal period. Gestational weight change in women with obesity can be flexibly modeled using latent classes, an important next step for prenatal weight change guidance. Funding Sources: ANDF, KPNC.